Challenges in International Service Learning - Nurbatra, Laela Hikmah (English Education: Jurnal Tadris Bahasa Inggris, 2018)
Benjamin Franklin said: “Tell me and I forget. Teach me and I remember. Involve me and I learn”. His statement emphasize the importance of involving students in their learning experience. International Service Learning, therefore, is regarded as a shift from traditional educational approach, which values the learning in a more meaningful way. With a real world experience, students in International Service Learning is argued to perform better, in their social, interpersonal, and intrapersonal skills (Cook-Sather, 2002; Larsen & Searle, 2017; Pratt & Danyluk, 2017, Carnicelli & Boluk, 2017 ). However, although international service learning has been conducted with adequate preparation, some issues are still identified (Darby, Ward-johnson, & Cobb, 2016; Larsen & Searle, 2017). In accordance to that, this paper highlights the challenges in the ISL program which administered by Faculty of Teacher Training and Education, University of Muhammadiyah Malang in qualitative method. In doing so, ten students involved in ISL program conducted in Thailand were selected as the research participants. In the results, the paper identify the challenges in three phase, namely pre-departure, during the implementation, and post-program. Furthermore, the paper provides the way to cope those challenges on each phase.